Oral microbiome dysbiosis in cryptogenic ischemic stroke patients with high-risk patent foramen ovale - Manzoor, Muhammed; Leskelä, Jaakko; Pietiäinen, Milla; Martinez-Majander, Nicolas; Könönen, Eija; Sinisalo, Juha; Putaala, Jukka; Pussinen, Pirkko J.; Paju, Susanna (Springer Science and Business Media LLC, 2025)
Patent foramen ovale (PFO) is the most common congenital heart abnormality of foetal origin and has been associated with cryptogenic ischemic stroke (CIS) through several mechanisms, with most theories supporting paradoxical embolism. Other possible but unknown contributing factors, such as the role of the microbiome in PFO-associated strokes, remain unclear. We analysed saliva metagenomes to study the differences in the oral microbiome between young-onset CIS patients with clinically relevant high-risk PFO (n = 52) and those without PFO (n = 52). Age- and sex-matched stroke-free controls (n = 16) with high-risk PFO were included for the comparison. Beta diversity was significantly different between patients and controls with high-risk PFO, but not between patients with and without high-risk PFO. The phylum Ascomycota and class Saccharomycetes were significantly more abundant in patients with high-risk PFO than in those without high-risk PFO. Additionally, the abundance of Lactococcus, including Lactococcus raffinolactis and L. cremoris, was higher in controls with high-risk PFO than in patients with high-risk PFO. These findings highlight that oral dysbiosis and high-risk PFO may form a critical but under-recognized combination in the aetiology of CIS. Future research should focus on elucidating the precise mechanisms of these interactions and developing targeted interventions.